Growth Response of Long Beans (Vigna unguiculata) and Mung Beans (Vigna radiata) to the Application of Different Types of Water - Fadia Khoirunnisa Sukowati; Lauren Felia Ramai; Widhi Ayu Arwani; Widya Krestina; Decenly, Decenly (Frontier Advances in Applied Science and Engineering, 2023)
Germination begins with imbibition or the entry of water that will activate various physiological components of the seed. So it is known that water has an important role in initiating the early stages of plant growth and development. The process of growth and development can be influenced by the type of water around it. This study aims to determine the growth response in Long Beans (Vigna unguiculata) and Mung Beans (Vigna radiata) to the application of various types of water, namely river water, peat water, rainwater and tap water. The seeds were soaked for 3 hours before planting. Then transferred to the planting media. Furthermore, for 7 days, observations were made along with watering the seeds using the treatment water. The parameters observed were the number of germinated seeds, sprout length, and root length on the seventh day. The data obtained were analyzed and processed using IBM SPSS software through parametric test (One-way ANOVA) and non-parametric test (Independent-Samples Kruskal-Wallis Test). Based on statistical tests, it is known that there is no significant difference, where in Long Beans the significance value is 0.795 (> 0.05). While in Mung Beans the significance value is 0.602 (> 0.05). The conclusion of this study is that there is no significant difference between each treatment, so that the various types of water in the treatment only as an initiator in the process of germination.